Comparability: manufacturing, characterization and controls, report of a UK Regenerative Medicine Platform Pluripotent Stem Cell Platform Workshop, Trinity Hall, Cambridge, 14–15 September 2015. (July 2016) - Williams, David J; Archer, Richard; Archibald, Peter; Bantounas, Ioannis; Baptista, Ricardo; Barker, Roger; Barry, Jacqueline; Bietrix, Florence; Blair, Nicholas; Braybrook, Julian; Campbell, Jonathan; Canham, Maurice; et al.
This paper summarizes the proceedings of a workshop held at Trinity Hall, Cambridge to discuss comparability and includes additional information and references to related information added subsequently to the workshop. Comparability is the need to demonstrate equivalence of product after a process change; a recent publication states that this 'may be difficult for cell-based medicinal products'. Therefore a well-managed change process is required which needs access to good science and regulatory advice and developers are encouraged to seek help early. The workshop shared current thinking and best practice and allowed the definition of key research questions. The intent of this report is to summarize the key issues and the consensus reached on each of these by the expert delegates.